Answer:
(x - 4)(x - 2)
x = 4
x = 2
Step-by-step explanation:
x² - 6x + 8
= (x - 4)(x - 2)
x - 4
x = 4
x - 2
x = 2
Step-by-step explanation:
Solve for xsin3⁡x+cos3⁡x=1" role="presentation" style="margin: 0px; padding: 0px; border: 0px; font-style: normal; font-variant: inherit; font-weight: normal; font-stretch: inherit; line-height: normal; font-family: inherit; font-size: 15px; vertical-align: baseline; box-sizing: inherit; display: inline; text-indent: 0px; text-align: left; text-transform: none; letter-spacing: normal; word-spacing: normal; overflow-wrap: normal; white-space: nowrap; float: none; direction: ltr; max-width: none; max-height: none; min-width: 0px; min-height: 0px; position: relative;">xsin3x+cos3x=1xsin3x+cos3x=1
sin3⁡x+cos3⁡x=1(sin⁡x+cos⁡x)(sin2⁡x−sin⁡x⋅cos⁡x+cos2⁡x)=1(sin⁡x+cos⁡x)(1−sin⁡x⋅cos⁡x)=1" role="presentation" style="margin: 0px; padding: 0px; border: 0px; font-style: normal; font-variant: inherit; font-weight: normal; font-stretch: inherit; line-height: normal; font-family: inherit; font-size: 15px; vertical-align: baseline; box-sizing: inherit; display: inline; text-indent: 0px; text-align: left; text-transform: none; letter-spacing: normal; word-spacing: normal; overflow-wrap: normal; white-space: nowrap; float: none; direction: ltr; max-width: none; max-height: none; min-width: 0px; min-height: 0px; position: relative;">sin3x+cos3x=1(sinx+cosx)(sin2x−sinx⋅cosx+cos2x)=1(sinx+cosx)(1−sinx⋅cosx)=1
Answer:
the answer the answer is the answer is C
Step-by-step explanation:
21 Unity
Answer:
61
Step-by-step explanation:
![a_{1}=5\\a_{n}=2a_{n-1}+3\\a_{2}=2*5+3=13\\a_{3}=2*13+3=29\\a_{4}=2*29+3=61](https://tex.z-dn.net/?f=a_%7B1%7D%3D5%5C%5Ca_%7Bn%7D%3D2a_%7Bn-1%7D%2B3%5C%5Ca_%7B2%7D%3D2%2A5%2B3%3D13%5C%5Ca_%7B3%7D%3D2%2A13%2B3%3D29%5C%5Ca_%7B4%7D%3D2%2A29%2B3%3D61)